2012
DOI: 10.1021/mz300078y
|View full text |Cite
|
Sign up to set email alerts
|

High Refractive Index Inorganic–Organic Interpenetrating Polymer Network (IPN) Hydrogel Nanocomposite toward Artificial Cornea Implants

Abstract: The use of artificial cornea implants has received increasing attention for treating cornea-related diseases and vision errors due to the low side effects. To achieve long-term successful vision correction, stable and biocompatible materials of high refractive index (RI) need to be developed. Herein, we developed an interpenetrating polymer network (IPN) hydrogel containing well-dispersed ZnS nanoparticles (∼3 nm) covalently linked to the first polymer network, poly(2-hydroethyl methacrylate) (PHEMA). The seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 23 publications
0
54
0
Order By: Relevance
“…It becomes extremely difficult to treat the defect or diseases associated to the eyes, and to design an implant or drug, which has the biocompatibility and mechanical properties similar to that of the natural eye. [181][182][183] Artificial cornea implants can be made of polymeric nanocomposites of having higher refractive index, 156,184,185 flexibility, 184,185 hydrophilicity, 184,185 and biocompatibility 184,186,187 as similar as that of human cornea. To achieve the refractive index approximately similar to that of natural eye, numerous efforts have been made by employing combination of different types of hydrophilic and hydrophobic copolymers.…”
Section: Polymer Nanocomposites For Ocular Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…It becomes extremely difficult to treat the defect or diseases associated to the eyes, and to design an implant or drug, which has the biocompatibility and mechanical properties similar to that of the natural eye. [181][182][183] Artificial cornea implants can be made of polymeric nanocomposites of having higher refractive index, 156,184,185 flexibility, 184,185 hydrophilicity, 184,185 and biocompatibility 184,186,187 as similar as that of human cornea. To achieve the refractive index approximately similar to that of natural eye, numerous efforts have been made by employing combination of different types of hydrophilic and hydrophobic copolymers.…”
Section: Polymer Nanocomposites For Ocular Applicationmentioning
confidence: 99%
“…For example, combination of various copolymer of n-butyl methacrylate (BMA), hexa(ethylene glycol) methacrylate (HEGMA) and polyurethane oligomer or interpenetrating polymer network (IPN) complemented with nanoparticles were found to accomplish desired higher level of refractive index so that the nanocomposites to be qualified as ocular implants. 156,184,185,188 Yet another factor that plays crucial part in the development of successful implants is their ability to absorb water. Traditionally, although the polymers selected for ophthalmological implants were able to reach reasonable refractive index, but the implants lacked in water absorption ability and flexibility.…”
Section: Polymer Nanocomposites For Ocular Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang and coworkers fabricated artificial cornea implants with ZnS nanoparticles inside two biocompatible polymers, poly(2-hydroethyl methacrylate) and poly(acrylic acid) [70]. They showed that this nanocomposite has a RI as high as 1.65, and performed various in vitro cell viability and cytotoxicity tests.…”
Section: A Refraction Index Modulation With Nanoparticlesmentioning
confidence: 99%
“…16, 30, 31, 41 The brittleness of the pure methacrylate network (i.e., 100% Methacrylate) is clearly evident in Figure 4A with a strain at break of 8.3 ± 1.2% in tension. In the IPN form, the brittle methacrylate network component is reinforced by the tough CuAAC component imparting the high toughness associated with it.…”
mentioning
confidence: 99%